Management of Patients with Differentiated Thyroid Carcinoma- SNMB Guidelines - Sultana, Sadia; Nahar, Nurun; Begum, Fatima; Alam, Faridul; Hasan, Mizanul; Hussain, Raihan; Haque, Mahmubul; Nasreen, Faria; Khan, Mohafizul Haque; Nisa, Lutfun; Moslem, Fauzia; Afroz, Shahana; et al. (Bangladesh Journal of Nuclear Medicine, 2017)
Abstract not available Bangladesh J. Nuclear Med. 18(1): 73-84, January 2015